The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1155/2014/231301
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Pearl Millet F1Hybrids for Heat Tolerance at Early Seedling Stage

Abstract: Ten pearl millet genotypes selected on the basis of response to supra-optimal temperature tolerance were crossed in a half-diallel mating system. The 45 F 1 hybrids produced were tested along with parents for heat tolerance and related traits at seedling stage. Field screening and laboratory screening techniques were simultaneously used for the evaluation of F 1 hybrids and their parents. Heat tolerance was measured as seedling thermotolerance index (STI) and seed to seedling thermotolerance index (SSTI) under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Furthermore, the relative yield superiorities were even larger in the lowest‐productivity conditions (Table 4), under which the majority of sorghum farmers in Mali grow sorghum (Leiser et al, 2012; Rattunde et al, 2016). Higher yield superiorities of hybrids over pure‐line check varieties under stressed environments were previously observed in sorghum (Haussmann et al, 1998) and other crops (Bidinger et al, 1994; Tollenaar and Wu, 1999; Betrán et al, 2003; Yadav et al, 2014).…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, the relative yield superiorities were even larger in the lowest‐productivity conditions (Table 4), under which the majority of sorghum farmers in Mali grow sorghum (Leiser et al, 2012; Rattunde et al, 2016). Higher yield superiorities of hybrids over pure‐line check varieties under stressed environments were previously observed in sorghum (Haussmann et al, 1998) and other crops (Bidinger et al, 1994; Tollenaar and Wu, 1999; Betrán et al, 2003; Yadav et al, 2014).…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, among three rice cultivars, F60 and F733 were more heat-susceptible than F473 when grown at 40 • C, with greater electrolyte leakage (20 and 15%) (Sanchez-Reinoso et al, 2014). Likewise, Yadav et al (2014) used CMT as an effective screening parameters for selecting heat tolerant lines in Pearl millet. From the same study, the authors also identified H77/29-2 × CVJ-2-5-3-1-3 hybrid as heat tolerance based on seedling thermotolerance index.…”
Section: Tissue Damagementioning
confidence: 99%
“…A better understanding of the impacts of climate on crop productivity is a basic requirement to enhance climate resilience in crop varieties through breeding or for adapting current varieties more resilient to climate induced stress through management options via various strategies to respond the contrary impacts of climate change on crop economic part (Barnabas et al 2008). Various tools can also be used in optimizing natural resources to assess the impacts of future impending climate on crop productivity (Yadav et al 2014).…”
Section: Introductionmentioning
confidence: 99%